Asynthesis, characterisation and biological activity of bismuth and antimony 1,1- dithiolates / Dyg Hazwani Abang Ishak - Dyg Hazwani , Abang Ishak (2017)
Motivated by the success of metal-based drugs in treatment of various diseases, 12 complexes of antimony (7-12) and bismuth (13-18) metal were synthesized and characterized by using 1HNMR, 13CNMR, FTIR, CHNanalyser, TGA, DSC, PXRD, SCXRD, UV-Visible and Fluorescence characterisation. After having verified the structure of the complexes, the prepared complexes were tested for their biological activity, anticancer in particular against a range of carcinoma cell lines, together with an evaluation of anti-microbial activities. Bismuth compound [Bi(S2CNR2)](13) with R=CH2CH3 was found to be cytotoxic towards an array of human carcinoma, more pronounced in HepG2 cells (liver cancer cells). This compoundalso induced apoptosis in the cell the death mechanism pathway and expressed death receptor-dependent pathway by generating CD40, CD40L and TNF-R1 (p55) protein. Moreover, complex 13 promotes tumour-suppressor, DAPK1 enzyme which naturally comes hand in hand with the down-regulation of XIAP gene and NF-?B, protein complex that controls the DNA transcription. The inhibition growth of HepG2 cells is in parallel with the findings that cell cycle arrest occurred at S and G2/M phases. However, another bismuth compound in the testing, [Bi(S2CNR2)] (16) with R=CH2CH2OH, is found to be less formidable in almost all of the study performed. This result is further supported by the cell invasion rate study whereby the invasion rate of 16 is 10-fold higher than that of 13, again, correlated with the down-regulation of XIAP and Survivin protein, extracted by 13. Complexes 13 and 16 were also discovered to have different binding motifs in DNA where 13 interacts at AT- and TA- specific sites followed by inhibition digestion of restriction enzyme; 16 display an adverse effect.